Driving Mechanisms for the Agricultural Tourism Network Sector in Phra Nakhon Si Ayutthaya Province - et. al., Thanaphum Pongsangiam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to study the driving mechanism for the agricultural tourism network sector in Phra Nakhon Si Ayutthaya province with the use of combined approaches. The 2 research processes comprised 1) to study of documents and related research with associate agricultural tourism network in Phra Nakhon Si Ayutthaya province and 2) to study of mechanisms to drive agricultural tourism with Delphi techniques from relevant sector, both public, private, public and academic. Results indicated that the driving mechanism for the agricultural tourism network sector in Phra Nakhon Si Ayutthaya province comprises the following elements 1. Man refers to a group of people or organization who join the network including 1) Government sector; 2) Private sector; 3) Public sector and 4) Academic sectors including educational institutes and related organization; .2. Resources refers to the tool used to promote the development of an area or a government network to support the development of the area, infrastructure to allocate budget to develop tourist attractions, private sector network to promote / support activities in the tourist area, public sector network to perform tourism resource management planning and academic sector network to support knowledge in development coordinating with relevant sector in the area for development and 3. Management System (System) refers to the establishment of a common agricultural tourism management model of network partners with the processes as follows: 1) Defining the needs to be a network; 2) Seeking partners to share information; 3) Forming a network to work 4) Setting goals, objectives, strategies that are common opinions; 5)Establishing working structure and share-decision making process; 6) Designing work plans and activities; 7) Developing network capacity; 8) Creating communication system; 9) Exchanging of knowledge and lesson summary development and 10) Monitoring and evaluation..